Dual anti-platelet therapy after coronary drug-eluting stent implantation and surgery-associated major adverse events - Egholm, Gro; Thim, Troels; Olesen, Kevin Kris; Madsen, Morten; Sorensen, Henrik Toft; Jensen, Svend Eggert; Jensen, Lisette Okkels; Botker, Hans Erik; Kristensen, Steen Dalby; Maeng, Michael (Thrombosis and Haemostasis, 2016)
Surgery may necessitate interruption of dual antiplatelet therapy (DAPT) within the first year after coronary drug-eluting stent (DES) implantation. We conducted a population-based cohort study to assess the rate of surgery within the first year after DES implantation, surgery-associated major adverse cardiac events (MACE), reoperation for bleeding within 30 days after surgery, and two nested case-control analyses to explore any association between preoperative antiplatelet therapy, MACE, and reoperation for bleeding. In the cohort of 22,654 patients treated with DES, 1,944 patients (8.6 %) underwent moderate- to high-risk surgery within 12 months. Of these, 62 (3.2 %) experienced MACE and 54 (2.8 %) needed reoperation for bleeding within 30 days. In the nested case-control analyses of 458 cases and controls, where 70 % (n=324) had a first generation DES, absence of preoperative antiplatelet therapy was associated with an increased MACE rate (OR 2.36, 95 % CI 1.02–5.48) compared to single antiplatelet therapy (SAPT) or DAPT. Preoperative SAPT versus DAPT showed no difference in MACE rates (OR 0.85, 95 % CI 0.30–2.40). Surgery within the first month was associated with increased MACE rate (OR 4.67, 95 % CI 2.22–9.83) compared to surgery 2–12 months after DES implantation. Absence of preoperative antiplatelet therapy did not reduce reoperation for bleeding as compared to patients on SAPT or DAPT (OR 1.32, 95 % CI 0.56–3.12). In conclusion, absence of preoperative antiplatelet therapy and surgery within the first month after DES implantation were associated with increased MACE rates.
Keywords: Antiplatelet agents; epidemiological studies; surgery; ischaemic heart disease